The Relationship of Demographic Factors with the Quality Management of Life of Diabetic Mellitus Patients in Hospital X - Fakhrudin Nasrul Sani; Puput Mulyono (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Sugar level disease or commonly called diabetes mellitus is a degenerative disease that rarely heals, often affecting health so that the quality of life can decrease. The purpose of writing this study is to find out what demographic relationship factors have an impact on the Quality of Life of Patients with Sugar Mellitus Disease or also known as Diabetes Mellitus at Hospital X. This quantitative research uses a research design on the cross sectional method. The research sample totaling 47 respondents was selected through total sampling techniques. Data was collected through the WHOQol-Bref survey instrument. The data analysis in this study applied the kendal test and the Chi-Square test to test the relationship between the variables studied. After the research was carried out, a result was obtained that showed demographic factors, namely the age factor to the quality of life had a relationship and as seen from the kendal test with a value of Sig. 0.003 which was below 0.05), other demographic factors there were gender factors that had a relationship with quality of life which was shown through the chi-square test where the Continuity Correction value sig = 0.022 < 0.05), In addition to demographic factors of age and gender, there are also demographic factors that have a relationship with quality of life, namely the work factor shown in the Chi-square Test with a value of Continuity Correction sig = 0.008 < 0.05), and there are demographic factors, namely education factors and marital status factors that are not related to the quality of life of people with sugar level disease or diabetes mellitus. For the education factor shown in the kendal test where the sig value = 0.871 > 0.05), and marital status is shown in the Chi-square test based on the Pearson Chi-Square Sig value = 0.594 > 0.05), there are also demographic factors that have a relationship with quality of life, namely the long-suffering factor shown by the Chisquare test with the Pearson Chi-Square Sig value = 0.014 < 0.05). To break the chain of diabetes mellitus, actions are carried out for health workers to be able to anticipate, including periodic socialization to the community about the dangers of diabetes mellitus so that it can help people improve their quality of life by maintaining a healthy diet.